2011
DOI: 10.1002/dc.21733
|View full text |Cite
|
Sign up to set email alerts
|

The cytomorphologic spectrum of salivary gland type tumors in the lung and mediastinum: A report of 16 patients

Abstract: In the lung and mediastinum, salivary gland type tumors (SGTTs) can occur as either primary tumors or metastases from tumors arising in the major or minor salivary glands. This study reviewed the cytology cases of SGTTs in the lung and mediastinum diagnosed over a six-year period at our institution. The specimens included a total of 22 exfoliative or aspiration cytology specimens identified in 16 patients. Two of the cases were primary tumors: adenoid cystic carcinoma (ACC) of the trachea and mucoepidermoid ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…reported that cytological findings of SDC in lung metastasis showed cohesive clusters of intermediate to large size with pleomorphic nucleus and glassy cytoplasm in a necrotic background. 7 These cytological findings were similar to those in our present case, however in our case we needed to distinguish primary lung adenocarcinoma from metastatic SDC, because SDC has a wide cytomorphologic spectrum. 9 ICC for AR antibody is a useful diagnostic tool to distinguish metastatic SDC from primary lung adenocarcinoma, because AR is highly expressed in approximately 80% of SDC, 9 but is only expressed in approximately 3.0% of primary lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…reported that cytological findings of SDC in lung metastasis showed cohesive clusters of intermediate to large size with pleomorphic nucleus and glassy cytoplasm in a necrotic background. 7 These cytological findings were similar to those in our present case, however in our case we needed to distinguish primary lung adenocarcinoma from metastatic SDC, because SDC has a wide cytomorphologic spectrum. 9 ICC for AR antibody is a useful diagnostic tool to distinguish metastatic SDC from primary lung adenocarcinoma, because AR is highly expressed in approximately 80% of SDC, 9 but is only expressed in approximately 3.0% of primary lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 89%
“…In cytology, bronchial brushing smears showed small sheet clusters in a slightly necrotic background, which was typical feature of adenocarcinoma. Monaco et al reported that cytological findings of SDC in lung metastasis showed cohesive clusters of intermediate to large size with pleomorphic nucleus and glassy cytoplasm in a necrotic background . These cytological findings were similar to those in our present case, however in our case we needed to distinguish primary lung adenocarcinoma from metastatic SDC, because SDC has a wide cytomorphologic spectrum .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The rate of recurrence of tumors presenting in parotid, submandibular, or sublingual glands was 36.4% and was not statistically significant ( P = .41) compared to the recurrence rates at all other sites of 24.2%. Distant metastasis were identified in the lungs and the liver …”
Section: Resultsmentioning
confidence: 99%
“…Occasional case reports exist of adenoid cystic carcinoma metastasizing to the pleural fluid,[91011] as well as a rare case of benign metastasizing pleomorphic adenoma[12] and a case of mucoepidermoid carcinoma involving peritoneal and pericardial fluid. [913] However, this appears to be the first case report of metastatic SDC in pleural fluid.…”
Section: Discussionmentioning
confidence: 99%